Historical Socio Analysis in the Interpretation of the Quran: Case Study of Legal Verses - Heri Khoiruddin; Rohimin Rohimin; Mohamad Anton Athoillah (UIN Sunan Kalijaga Yogyakarta, 2019)
This study is to find the role of historical setting of the Quran revelation in understanding Quran, which is traced through the cause of Quran revelation. The verses analyzed in this study are the verses of the law (legal verses) which have the special cause of revelation. Those verses of the law are read and interpreted by using three theory of the cause of revelation, those are the common word of the Quran text, the special cause of revelation, and maqāsid al-sharīa (purposes of sharia). The finding of this study asserts that the verses of the law which are read and interpreted by using maqāsid al-sharīa are more dynamic than using two other theories. Based on this finding, then any provision of the law which differ textually with the provision of the law existing in the Quran may it is a part of the Quran teaching based on the similarity of maqāsid al-sharīa.[Penelitian ini bertujuan untuk mengetahui peranan latar historis turunnya ayat dalam memahami Alquran, yang ditelusuri melalui sebab turunnya ayat. Ayat-ayat yang dianalisis pada penelitian ini adalah ayat-ayat hukum yang memiliki sebab turun khusus. Ayat-ayat tersebut dibaca dengan kaidah sebab turun yang dibaca dengan menggunakan tiga kaidah sebab turun, yakni keumuman lafal, kekhususan sebab, dan maqāsid al- sharīah (tujuan-tujuan syara). Simpulan penelitian ini mengatakan bahwa ayat-ayat hukum yang dibaca menggunakan maqasahid syariah lebih dinamis daripada ayat-ayat hukum yang dibaca menggunakan kekhususan sebab apalagi keumuman lafal. Didasarkan pada simpulan ini, maka setiap ketetapan hukum yang berbeda secara tekstual dengan ketetapan hukum yang ada dalam Alquran boleh jadi merupakan bagian dari ajaran Alquran didasarkan pada kesamaan maqāsid al-sharīah.]